The impact of columnar and equiaxed β-grain structures on mechanical anisotropy in high-deposition-rate additively manufactured α + β titanium alloys - Davis, Alec E.; Donoghue, Jack; Kennedy, J.; Atkinson, M. D.; White, M.; Neto, Leonor; Biswal, Romali; Caballero, Armando E.; Zakir, F.; Syed, Abdul Khadar; Zhang, X.; Williams, Stewart; et al. (Springer, 2026)
There is growing interest to produce α + β titanium alloys with high-deposition-rate additive manufacturing (DED-AM) processes for aerospace applications. However, there are still important aspects of their microstructure-mechanical property relationships that are not well understood, which are linked to the macro and microstructure heterogeneities generated by the AM processes and intrinsic titanium metallurgy that produce columnar β-grain structures. Trends in the literature, which are based primarily on Ti-6Al-4V data, have shown mechanical anisotropy is often present when samples exhibit coarse and columnar β-grain structures. This includes yield-stress and elongation anisotropy arising during uniaxial tensile testing, and crack growth rate anisotropy with high scatter recorded during fatigue testing, both of which are generally only tested in orientations parallel and perpendicular to the AM build direction. In this work, this mechanical anisotropy in α + β titanium alloys is investigated in more detail with Ti-6Al-4V and Ti-6Al-2Sn-4Zr-2Mo-0.1Si wire-arc additively manufactured test samples, comparing columnar parent β-grain structures to equiaxed grain structures. In particular, highlighting that the true yield-stress anisotropy in columnar grain samples is only revealed when testing the material at a 45 deg orientation away from the AM build direction. It is also shown that the large grain boundary α colonies that form on parent columnar β-grain boundaries have a significant impact on the fatigue crack growth rate data scatter. Refining the parent β-grain structures is demonstrated to resolve these issues and the related microstructure mechanisms were investigated in detail, using both experimental and crystal plasticity simulation methods. Finally, the formation and three dimensionality of the detrimental grain boundary α colonies that nucleate on columnar β-grain boundaries were investigated for the first time using in-situ SEM heating and 3D-EBSD techniques.
Keywords: 4014 Manufacturing Engineering; 40 Engineering; Materials; 4016 Materials engineering; 4017 Mechanical engineering